2019
DOI: 10.1103/physrevd.99.063525
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-void degeneracy breaking: Neutrino properties and dark energy

Abstract: Future large-scale spectroscopic astronomical surveys, e.g. Euclid, will enable the compilation of vast new catalogues of clusters and voids in the galaxy distribution. By combining the constraining power of both cluster and void number counts, such surveys could place stringent simultaneous limits on the sum of neutrino masses Mν and the dark energy equation of state w(z) = w0 + waz/(1 + z). For minimal normal-hierarchy neutrino masses, we forecast that Euclid clusters + voids ideally could reach uncertaintie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 45 publications
0
38
0
1
Order By: Relevance
“…Indeed recent work showed that the cosmological bounds on M ν are weaker when one enlarges the parameter space to other values of w(z) including phantom values w < −1. In fact there exists a well-known degeneracy between the DE EoS w and the sum of the three active neutrino masses M ν [66,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114]. However, the main result of our paper is that the cosmological bounds on neutrino masses in fact become more restrictive for the case of a DE component with w(z) ≥ −1 than for the standard ΛCDM case of w = −1.…”
Section: Introductionmentioning
confidence: 85%
“…Indeed recent work showed that the cosmological bounds on M ν are weaker when one enlarges the parameter space to other values of w(z) including phantom values w < −1. In fact there exists a well-known degeneracy between the DE EoS w and the sum of the three active neutrino masses M ν [66,[99][100][101][102][103][104][105][106][107][108][109][110][111][112][113][114]. However, the main result of our paper is that the cosmological bounds on neutrino masses in fact become more restrictive for the case of a DE component with w(z) ≥ −1 than for the standard ΛCDM case of w = −1.…”
Section: Introductionmentioning
confidence: 85%
“…when the dark energy equation of state is allowed to vary), see e.g. [18,22,23,29,30,[43][44][45][46][47][48] for recent investigations, although there are exceptions to this statement: for instance, allowing for a time-varying dark energy component, but forcing it to lie in the non-phantom region (i.e. w(z) ≥ −1), actually results in tighter upper limits on M ν [49].…”
Section: Introductionmentioning
confidence: 99%
“…We consider a flat wCDM cosmology with massive neutrinos described by the sum of neutrino masses m ν . The void distribution is modelled following Sahlén et al (2016), Sahlén & Silk (2018), and Sahlén (2019), also taking into account the galaxy density and bias for each survey (Yahya et al 2015;Raccanelli et al 2016c). The results are shown in Figure 35 (see caption for survey and model assumptions).…”
Section: Constraining Neutrino Properties With Ska Voidsmentioning
confidence: 99%
“…The SKA2 void number counts could improve on this, down to σ (γ 0 ) = 0.07, σ (γ 1 ) = 0.15. Using the powerful degeneracy-breaking complementarity between clusters of galaxies and voids (Sahlén et al 2016;Sahlén & Silk 2018;Sahlén 2019), SKA2 voids + Euclid clusters number counts could reach σ (γ 0 ) = 0.01, σ (γ 1 ) = 0.07.…”
Section: Radio Weak Lensingmentioning
confidence: 99%